Hong Kong : The monocle travel guide series - Monocle, ....- (Berlin : Gestalten, 2015)
Vertigo-inducing skyscrapers that cling to mountainous slopes and busy fishing villages that proudly hold on to their cultural heritage: Hong Kong is more diverse than you'd imagine.
Keywords: reisgids